Treatment of hepatic hydatidosis by radical surgery: Our experience - Delgado, Bolívar (Cirugía del Uruguay, 1991)
The author presents his clinic's experience in the treatment of hepatic hydatidosis by radical procedures. 42 of these procedures were carried on in 39 patients with a mortality of 5, 1 % and an average post-operative hospitalization of 13 days. This treatment is analysed by comparing it to national and foreign series.